ANALISIS PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN SEKTOR PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2012-2016 - Hendratni, Tyahya Whisnu; Nawasiah, Nana; Indriati, Trisnani (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to examine the effect of the board of commissioner's size, the board of directors, institutional ownership, independent commissioner; and firm size on financial performance. The population used in this study is a banking company listed on the Indonesia Stock Exchange period 2012 - 2016. The population of this study amounted to 144 companies. Sampling was done using non-random sampling technique. There are 20 companies that meet the criteria as research samples so that the research data amounted to 100. Data analysis is multiple linear regression tests. The results of this study show the board of commissioners, institutional ownernship, and independent commissioner have a positive effect, while firm size has a negative effect on financial performance. Keywords: corporate governance, financial performance